ADMISSIBILITY OF EVIDENCE AS A FEATURE OF EVIDENCE IN CRIMINAL PROCEEDINGS - Mamatkulova, Khosiyat (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The institution of admissibility of evidence as a fundamental category of the criminal process has been discussed in the article. The author discussed issues such as the nature of evidence, its properties and conditions of admissibility in criminal proceedings. The author emphasizes that the admissibility of evidence not only protects the rights of participants in the process, but also affects the final court decision. Foreign experience and legislation were also studied and discussed.